2021
DOI: 10.1094/pdis-07-20-1527-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bacterial Leaf Spot Disease of Broussonetia papyrifera Caused by Pseudomonas syringae pv. actinidiae in China

Abstract: Broussonetia papyrifera (paper mulberry) is a deciduous tree with a number of uses and is native to northeastern Asia. Because of its fast-growing nature and high tolerance to dust, smoke, and high temperatures, paper mulberry is regarded as an important and economically-valuable component of a biologically diverse community and is used extensively in several areas including medicine, animal husbandry, paper making, weaving, afforestation and light industry (Mei et al. 2016). From June to August of 2019, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Undoubtedly, genetic transfer among Psa populations would further accelerate its diversity with potential changes in ecological fitness, virulence, and host range. In fact, it has been recently reported that Psa can cause leaf spot disease on Broussonetia papyrifera (an economic tree species) grown nearby kiwifruit orchards [ 29 ], suggesting a possible expansion of the Psa host range.…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly, genetic transfer among Psa populations would further accelerate its diversity with potential changes in ecological fitness, virulence, and host range. In fact, it has been recently reported that Psa can cause leaf spot disease on Broussonetia papyrifera (an economic tree species) grown nearby kiwifruit orchards [ 29 ], suggesting a possible expansion of the Psa host range.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the accurate identification of the bacterial pathogen, sufficient knowledge of its life cycle is of utmost importance to anticipate potential disease outbreaks and plan the most efficient management strategies to contain its local and global dissemination. In the case of Psa, its main hosts are the species from the genus Actinidia, with very few reports of its presence in non-kiwifruit plants [12,37,38]. As with other pathogenic pseudomonads, Psa infection begins with bacteria entering the host plant through natural openings (e.g., stomata, lenticels, broken trichomes and hydathodes), natural wounds (e.g., wind damage) and artificially made wounds (e.g., pruning, and girdling activities) [12,39,40].…”
Section: Understanding Pathogen Epidemiologymentioning
confidence: 99%
“…For example, Psa was found living epiphytically on Cryptomeria japonica, often used as shelterbelts in kiwifruit orchards in New Zealand, surviving up to 14 days when artificially inoculated [123]. Psa was also isolated from Setaria viridis, Alternanthera philoxeroides, Paulownia tomentosa, and Broussonetia papyrifera, which inclusively presented the same characteristic disease symptoms [37,38]. Several nonhost plants collected in proximity to infected kiwifruit plants, including Calystegia sylvatica and Capsella bursa-pastoris, have also shown potential for harboring Psa [12].…”
Section: Agronomical Practicesmentioning
confidence: 99%
“…mori (bacterial blight of white mulberry), and pv. persicae (bacterial decline of stone fruit) (Alippi et al, 2013; Cunty et al, 2015; Green et al, 2009; Krawczyk & Łochyńska, 2020; Li et al, 2020a; Rodrigues et al, 2017; Scortichini et al, 2012; Vanneste et al, 2013; Young, 2014). The pv.…”
Section: Phages For Treatment Of Bacterial Tree Diseasesmentioning
confidence: 99%